MANEJO DA BATATA-DOCE NO CONTROLE DA BROCA-DA-RAIZ, A NÃVEL DO PRODUTOR - Andrade, Marcelo Bezerra de; Veiga, Antônio Fernando de Souza Leão (REVISTA DE AGRICULTURA, 2015)
MANEJO DA BATATA-DOCE NO CONTROLE DA BROCA-DA-RAIZ, A NÃVEL DO PRODUTOR